Evaluation of a one-dose package medication support system for community-based elderly patients and eldercare facilities. (1st May 2018) - Suzuki, Ryoji; Hasegawa, Takashi
Abstract : Purpose: Results of an evaluation of a one-dose package medication support system (ODP-MSS) for medication support and telecare home monitoring of elderly persons are reported. Methods: ODP-MSS units were provided to 10 elderly patients living at home, with adherence assistance provided by family members or other medication supporters in response to telephone alerts. In addition, ODP-MSS units were installed in 2 group homes. At the end of the designated study periods, device data logs were analyzed, and study participants were interviewed or surveyed regarding the impact of ODP-MSS use. Results: Overall, 2 patients were reported to have missed medication doses due to forgetfulness; in both cases, alerted medication supporters called the patients and reminded them to take their medicine. Five home-dwelling patients and 5 supporters reported that the ODP-MSS provided useful reminders; 4 patients and 7 supporters indicated that calls to supporters were useful as a telecare home monitoring system. Eleven group home staff members reported that the ODP-MSS was useful in reducing medication errors and the need for medication assistance. Conclusion: An ODP device plus follow-up calls from a medication supporter helped prevent missed doses resulting from patients' forgetfulness and may serve as a useful component of telecare home monitoring for elderly people living independently at home. The ODP device was also useful for reducing the burdens associated with medication support and medication errors on staff members of group homes for elderly patients with dementia.